2021
DOI: 10.5606/tftrd.2021.6775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scapular stabilization exercises in patients of chronic neck pain with scapular dyskinesis: A quasi-experimental study

Abstract: Objectives This study aims to investigate the effectiveness of scapular stabilization exercises in patients with chronic neck pain and scapular dyskinesis. Patients and methods This single-center, prospective study included a total of 36 patients (17 males, 19 females; mean age: 41±12.8 years; range, 25 to 57 years) with chronic neck pain and scapular dyskinesis between April 2018 and September 2018. The patients were randomly assigned to three treatment groups. Group 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Although a significant improvement was observed in Neck Disability Index scores after six weeks of training in both groups, there was no significant difference in scapula kinematics between the intervention and control groups. 41 Jordan et al suggested that the gain in strength in these subjects was likely a result of increased confidence. Ylinen et al28 explained that the strength increase in the control group was probably due to biologic variation and learning effect due to repeated testing.…”
Section: Discussionmentioning
confidence: 96%
“…Although a significant improvement was observed in Neck Disability Index scores after six weeks of training in both groups, there was no significant difference in scapula kinematics between the intervention and control groups. 41 Jordan et al suggested that the gain in strength in these subjects was likely a result of increased confidence. Ylinen et al28 explained that the strength increase in the control group was probably due to biologic variation and learning effect due to repeated testing.…”
Section: Discussionmentioning
confidence: 96%
“…duplicate options, nonpaper articles such as reviews and conference articles and irrelevant studies were removed rst. Finally, 8 studies [21][22][23][24][25][26][27][28] were selected for further evaluation and data analysis after excluding articles that did not meet the criteria of our purpose.…”
Section: Study Selectionmentioning
confidence: 99%
“…All 8 RCTs [21][22][23][24][25][26][27][28] published in English between 2016 and 2023 were included in the meta-analysis, which was conducted in Asia (Kingdom of Saudi Arabia [21] , Korea [22] and Iran [23,25−27] ) and Europe (Turkey [24,28] ). A total of 313 participants were enrolled, and the sample sizes of these studies ranged from 15 to 87 studies [21][22][23][24][25][26][27][28] recruited patients with CNP that persisted for 3-6 months in the neck region. Some of the neck pain patients in these included studies also had problems with abnormal shoulder and neck posture [22,25,27] or scapular movement [21,24,26,28] .…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scapular stabilization exercise (SSE) is a method designed to secure the scapula in the neutral position of the thoracic cage through the interaction of the muscle that makes up the shoulder [17]. SSE is an exercise to position the scapula between the 2 nd and 7 th ribs, which is the neutral point of the chest, through the interaction of the muscles around the shoulder joint that connects the upper limbs and trunk [18][19][20]. It has recently been viewed 1 shows the characteristics of the subjects.…”
Section: ⅰ Introductionmentioning
confidence: 99%